Arrangement of Physical Test Instrument for Tarung Derajat in Adult Category - Gideon Elyfelet Ndaumanu; Awan Hariono (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to (1) produce a physical test instrument for combat martial arts in the adult fighting category (2) produce a manual for a physical test instrument in the adult fighting category. (3) Knowing the feasibility of the product manual for the physical test instrument for combat martial arts degrees in the adult fighting category.This research is a type of research (R&D) using the 4D development model. This development model consists of four stages: (define, design, develop, disseminate). This research was conducted at PB Kodrat Yogyakarta which involved two validators, 1 material expert and 1 physical condition expert, 3 practitioners and 2 colleagues and 10 combat trainer respondents. The data collection technique used a questionnaire, the Delphi method, and an assessment rubric. The validity test uses content validity which is analyzed using the aikens v formula and concurrent validity which is analyzed using product moment correlation. Reliability test using Apha Cronbach. This research resulted in a physical test manual for the adult fighting category, which consisted of 12 test items, namely: (1) side split, (2) 20 meter sprint, (3) hexagonal obstacle, (4) standing broad jump, ( 5) shock test (6) Expanding Dynamometer (7) leg dynamometer (8) back leg dynamometer (9) 1 minute push ups, (10) 1 minute sit ups, (11) wall squat test, (12) run 2.4 km. The physical test instrument for fighting martial arts degrees is declared valid with r count > from r table with details; 0.94 > 0.632 and the test was declared reliable with Cronbach's alpha value of 0.945 > 0.765. The product of the physical test instrument for Tarung Degrees has a feasibility percentage of 100% with a very strong/decent/appropriate category from a material expert and 100% very strong/appropriate/feasible. from a physiotherapist. The trainer's response to the manual has a percentage of 96% including in the very very strong / appropriate / appropriate category.